Home Literacy Environment and Children’s Literacy Skills in Grade 2 - Šilinskas, Gintautas; Raižienė, Saulė (Vilnius University Press, 2026)
We investigated the extent to which different aspects of home literacy environment (HLE) relate to literacy skills among Grade 2 students in Lithuania. The participants were Lithuanian second-graders (n = 522; 48% girls; Mage = 8.29 years, SD = .32) and their parents (88.3% mothers). Children were tested in their language and literacy skills; whereas parents completed questionnaires concerning HLE. We ran three hierarchical regression models to predict children’s sentence reading fluency, spelling to dictation, and reading comprehension. Control variables (parental education, child gender, vocabulary and word reading fluency) were entered at the first step; the four variables of HLE (teaching of literacy, reading to a child, access to literacy resources, child’s own independent reading) were entered at the second step. The results showed that HLE variables added a significant amount of explained variance to the regression models (5.4% for sentence reading fluency, 4.8% for spelling, and 4.9% for reading comprehension). Overall, the results suggest that in order to promote children’s literacy skills in Grade 2 most effectively, parents should provide access to literacy resources and create opportunities for children’s independent reading. When considering all HLE factors together in one analysis, children’s actual independent reading of the reading materials emerged as an important factor in their success in reading and spelling.